A Practical Approach to Bicyclic Carbamoyl Pyridones with Application to the Synthesis of HIV-1 Integrase Strand Transfer Inhibitors - Pankaj S. Mahajan; Steven J. Smith; Stephen H. Hughes; Xuezhi Zhao; Terrence R. Burke (Molecules, 2023)
An efficient one-pot synthetic method has been developed for the preparation of bicyclic carbamoyl pyridones from the known common intermediate methyl 5-((2,4-difluorobenzyl)carbamoyl)-1-(2,2-dimethoxyethyl)-3-methoxy-4-oxo-1,4-dihydropyridine-2-carboxylate (8). The scalable protocol is facile and employs readily available reagents, needing only a single purification as the final step. The utility of the approach was demonstrated by preparing a library of HIV-1 integrase strand transfer inhibitors (INSTIs) that differ by the presence or absence of a double bond in the B-ring of the bicyclic carbamoyl pyridines 6 and 7. Several of the analogs show good antiviral potencies in single-round HIV-1 replication antiviral assays and show no cytotoxicity in cell culture assays. In general, the compounds with a B-ring double bond have higher antiviral potencies than their saturated congeners. Our methodology should be applicable to the synthesis of a range of new metal-chelating analogs.